(untitled) (Società e diritti, 2025)
The article explores the complex relationship between torture, human dignity, and the law. It discusses how torture inflicts severe physical and mental suffering, undermining the victim’s integrity and depersonalizing them. The text highlights the legal, moral, and political implications of torture, emphasizing its role as a fundamental evil that distorts the law and truth. The document contrasts the pathic environment, where individuals are recognized in their existential entirety, with the apathetic environment, where torturers operate. It delves into the temporal aspect of torture, describing the prolonged agony experienced by victims and the torturer’s gaze, which immortalizes their suffering. The conclusion calls for recognizing the corporeality and dignity of individuals, advocating for a culture of dignity that respects human beings’ existential entirety and preserves the memory of victims.